Clinicopathologic Features Of Colorectal Cancer At RSUD Dr. H. Chasan Boesoirie Ternate 2018-2023 - Santy, Sulthana Tiara; Djafar, Nurdhani H; M. Selomo, Prita Aulia (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
According to the International Agency for Research on Cancer (IARC), colorectal cancer or colon cancer includes cancer of the colon and rectum. Colorectal cancer is the 3rd most common cancer and the 4th most common cause of death related to cancer and according to GLOBOCAN in 2020 CRC is the 2nd most cases of death. The purpose of this study is to determine how the clinicopathological Features of colorectal cancer at RSUD Dr. H. Chasan Boesoirie ternate in 2018-2023, based on parameters such as age, gender, histopathology type, degree of differentiation, clinical symptoms, and cancer location. This study is an observational descriptive study with a cross-sectional approach. The sample of this study amounted to 29 samples, taken using total sampling technique. The results of the study are 29 cases where most were in the age range of 51-60 years namely 10 cases (34.5%), with 16 cases (55.2%) were males. The most clinical symptoms are bloody stools, as many as 14 cases (48.3%), and most located in the rectum, namely 15 samples (51.7%), In addition, the most common histopathological type is adenocarcinoma as many as 25 samples (86.2%) followed by the degree of tumor differentiation are well-differentiated, which was the most cases namely 22 samples (72.9%). Most cases were in the age range of 51-60 years with male gender and bloody stool as clinical symptoms, most located in the rectum with histopathology type mostly are adenocarcinoma well-differentiated. Keyword: adenocarcinoma; colorectal cancer; clinicopathology